User characteristics of national smoking cessation services in Korea: who chooses each type of tobacco cessation program? - Bo Yoon Jeong; Min Kyung Lim; E. Hwa Yun; Jin-Kyoung Oh (BMC, 2019)
Abstract Background Relatively little is known about which characteristics of smokers are related to choosing a specific type of smoking cessation service. The user characteristics of different smoking cessation services were compared to determine the service preferred by user characteristics. Methods The characteristics of adult smokers from Korea National Health and Nutrition Examination Survey (3762) and registered users of national smoking cessation services operated through the web (14,762), at Public Health Center-based Smoking Cessation Clinics (PHC-based SCCs) (335,532), and by telephone (Quitline) (2983) were compared. Results Females and younger aged were more in web and telephone-based cessation service users, while aged 50 years or older were more in PHC-based SCCs users. Although manufacturing and production workers were the most prevalent among smokers in the general population, office workers and others including housewives and unemployed were most prevalent among the users of Quitline and PHC-based SCCs, respectively. The number of cigarettes smoked per day was twice as high among cessation service users as in general population. Smokers with greater nicotine dependency were most prevalent in the web-based service. Overseas users were in the web-based cessation service. Conclusion Identifying user-specific characteristics by the type of cessation services looks necessary to develop and offer appropriate cessation services.